2020
DOI: 10.1101/2020.10.28.359034
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced neural tracking of the fundamental frequency of the voice

Abstract: 'F0 tracking' is a novel method that investigates the neural processing of the fundamental frequency of the voice (f0) in continuous speech. Through linear modelling, a feature that reflects the stimulus f0 is predicted from the EEG data. Then, the neural response strength is evaluated through the correlation between the predicted and actual f0 feature. The aim of this study was to improve upon this 'f0 tracking' method by optimizing the f0 feature. Specifically, we aimed to design a feature that approximates… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…size f = 0.98; imagery: p = 2.7 Â 10 -209 common language effect size f = 0.97; see Materials and Methods). The note onset encoding was significant at the individual participant level (17 of 21, p , 0.05, FDR-corrected p values extracted from the null model distributions) and was most accurately encoded on central scalp areas, as previously shown in response to auditory experiments (Di Liberto et al, 2020a,b;Van Canneyt et al, 2020). A significant (p = 0.02) correlation of r = 0.3 was measured between the topographies of the EEG prediction values for the two conditions (Pearson's correlation).…”
Section: Onsets Encodingsupporting
confidence: 71%
“…size f = 0.98; imagery: p = 2.7 Â 10 -209 common language effect size f = 0.97; see Materials and Methods). The note onset encoding was significant at the individual participant level (17 of 21, p , 0.05, FDR-corrected p values extracted from the null model distributions) and was most accurately encoded on central scalp areas, as previously shown in response to auditory experiments (Di Liberto et al, 2020a,b;Van Canneyt et al, 2020). A significant (p = 0.02) correlation of r = 0.3 was measured between the topographies of the EEG prediction values for the two conditions (Pearson's correlation).…”
Section: Onsets Encodingsupporting
confidence: 71%
“…More complicated and computationally expensive techniques have also been explored, including empirical mode decomposition (Etard et al, 2019; Forte et al, 2017) and auditory modelling (Van Canneyt et al, 2021b). Constructing an f0 feature that approximates the expected neural response using auditory modelling has proven particularly effective, nearly doubling the reconstruction accuracies obtained with the neural tracking analysis (Van Canneyt et al, 2021b). This is likely explained by the fact that the auditory model is more physiologically valid.…”
Section: Neural Tracking Of the F0mentioning
confidence: 99%
“…The original algorithm for computing the fundamental waveform was based on empirical mode decomposition (Huang and Pan (2006); Forte et al (2017)). However, Etard et al (2019) showed that direct band-pass filtering of the speech signal is considerably simpler, faster to compute and leads to the same result (Kulasingham et al (2020); Van Canneyt et al (2021b,a); Bachmann et al (2021)). Here, we also employed a band-pass filter to extract the fundamental waveform from the voice recordings.…”
Section: Methodsmentioning
confidence: 99%